Sense and Non-Sense in Contemporary Ethno/Graphic Practice and Theory - Howes, David (Culture, 1991)
This essay presents an overview and critique of the “textual revolution” in anthropological theory and practice. The author argues that this revolution, which commenced with Geertz′s suggestion that cultures be treated “as texts” and culminated in Writing Culture, has precipitated a flight from theory to style. It is further argued that anthropologists should abandon “the model of the text” and re-learn how to use their senses. Various examples are given of how a more in-depth understanding of cultures can be achieved by sensing them than reading/writing them.